Subsurface temperature change attributed to climate change at the northern latitude site of Kapuskasing, Canada - Novara, Ivan Lionel (2024)
Subsurface temperatures have been measured in different regions of the world, usually near the surface up to a depth of about a hundred meters. In this work a forward model calculation for a Northern Hemisphere soil temperature site at Kapuskasing, Canada, is presented, employing the solution of the differential equation of heat conduction through a semi-infinite homogeneous solid, subject to surface boundary conditions determined by surface air temperature. In this way, a detailed analysis is made of the subsurface temperature as a function of ground depth and for the time interval ranging from 1970 to the future (including the next century), for different scenarios of climate change. From these results, it was possible to determine the following characteristic quantities: (a) the depth where the surface perturbation (practically) finishes (in the range of about 180-200 m); (b) the depth where the subsurface temperature changes its slope from negative to positive; (c) the temperature change at the surface for the years where data exist; (d) the thermal gradient at steady state in the starting year (1880); (e) the temperature differences extrapolated at surface and at a 20 m depth, this last value corresponding to the depth at which seasonal and diurnal temperature variations are negligible; (f) the heat flow at surface to the inner part of the soil attributed to climate change, and (g) the temperature changes at surface for the 100 years interval (1980-2080) and mainly for the next century (2080-2180), for each site and for each IPCC Representative Concentration Pathway (RCP) scenario. As an example, the impact of the change in mean annual soil temperature due to global warming in near-surface geothermal energy is described.